Quality services as perceived by students of international and public schools - Hoque, Kazi Enamul (Marsland Press, 2013)
In today’s world of global competition, rendering quality service is a key for success. The aim of this study was to compare the quality of service delivery between Saudi and Malaysian public Schools operated in Kuala Lumpur, Malaysia. In this research, there are five important factors the researcher used to examine the service delivery in both Malaysian and Saudi schools through student perception namely (1) physical evidence, (2) contact personnel, (3) reputation and assessment, (4) admission, and (5) teaching and teachers. Quantitative approach is used in this study. Responses from 250 students are analysed. The result shows that Malaysian students had lower satisfaction than Saudi ones on the service delivery in their schools in all six factors mentioned above. All the mean scores of Malaysian school are lower than the Saudi. There is also found significant difference of the satisfaction with the service delivery between Malaysian and Saudi students. It is suggested that public Malaysian schools consider the service delivery weakness and find the solutions for them even the schools are mostly supported by the government.